2016
DOI: 10.1111/jgs.13944
|View full text |Cite
|
Sign up to set email alerts
|

Frailty Trajectories in an Elderly Population‐Based Cohort

Abstract: BACKGROUND/OBJECTIVES Little is known about longitudinal changes in frailty and how these changes impact adverse outcomes in elderly patients. Thus, we identified distinct frailty trajectories (clusters of individuals following a similar progression of frailty over time) in an aging population and estimated associations between frailty trajectories and emergency department visits, hospitalizations, and all-cause mortality. DESIGN Population-based cohort study SETTING Olmsted County, Minnesota PARTICIPANT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
54
1
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 34 publications
6
54
1
9
Order By: Relevance
“…Recent studies found that morbidity and multiple morbidities at younger ages strongly predict increasing morbidities with aging. 36,37 In all reported studies, patients with zoster have greater numbers of chronic conditions at the time of zoster compared to age- and sex-matched controls. Thus, it is possible that an increased long-term risk of MI and stroke is due at least in part to the steeper multi-morbidity trajectory in zoster patients.…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies found that morbidity and multiple morbidities at younger ages strongly predict increasing morbidities with aging. 36,37 In all reported studies, patients with zoster have greater numbers of chronic conditions at the time of zoster compared to age- and sex-matched controls. Thus, it is possible that an increased long-term risk of MI and stroke is due at least in part to the steeper multi-morbidity trajectory in zoster patients.…”
Section: Discussionmentioning
confidence: 95%
“…Sedentary behaviour is an imminent risk factor that has gained attention in the literature. It is a consensus that this behavioural aspect is associated with deleterious health effects [29,30], including risk for all-cause mortality [4,31] and frailty [11]. …”
Section: Discussionmentioning
confidence: 99%
“…Experts in the subject indicate that this outcome is a complex, dynamic concept that involves a state of greater vulnerability to adverse health factors, including those that are associated with falls, fractures, disability and health status [1,2,3], and that frailty increases the chances of morbidity and mortality [4]. …”
Section: Introductionmentioning
confidence: 99%
“…2001; Morley et al ., 2013; Chamberlain et al ., 2016). Together, these serve to limit mobility, independence, and the ability to perform activities of daily living in older adults (Chamberlain et al ., 2016). In this review, we describe the underlying inflammatory phenotype associated with frailty and speculate how it may be linked to the inflammatory phenotype that occurs with HF.…”
Section: Definition Of Frailtymentioning
confidence: 99%